Lecturers’ Experiences with Artificial Intelligence in Arabic Language Education: A Narrative Inquiry - Riska Khairani Nasution; Zubaidah; Luluk Yuliani; Siti Aisa Sanif; Zuyyina Ilmy Azizah (Indonesian Journal of Arabic Education and Learning, 2026)
This study explores a lecturer’s lived experiences in navigating the presence of generative artificial intelligence (AI) within Arabic language education. Using a narrative inquiry approach, the research examines how a lecturer in an Islamic university encounters AI in daily teaching practices, responds to students’ increasing reliance on AI tools, and makes meaning of the ethical complexities that arise from this shift. Data were collected through an in-depth semi-structured interview with one participant and analyzed thematically. The findings reveal that AI has transformed students’ writing and translation behaviors, making their work more structured yet increasingly dependent on automated outputs. While the lecturer acknowledges AI’s potential to assist learning and streamline explanation, concerns emerged regarding plagiarism, diminished original contribution, and weakened critical thinking. AI was perceived not merely as a technical assistant, but as a presence that challenges pedagogical judgment, ethical boundaries, and core values of Islamic education such as honesty, amanah, and adab belajar. This study contributes to the growing discourse on human centered AI integration in Arabic language education by highlighting the ethical reflections and practical decisions educators must negotiate. Future research may broaden participant perspectives and observe long-term changes in teaching practices shaped by AI.